A loose and damaged sculpture of Nandi - Temples of India Project Team (Jio Institute, 2024)
A loose and damaged sculpture of Nandi found in the vicinity of the Neelkanth Mahadev Temple. Since the central shrine in Neelkanth Mahadev Temple is dedicated to Shiva, the presence of this Nandi sculpture is noteworthy. Though the original location of this sculpture is not known, it might have been inside the mandapa (pillared hall) of the temple.